Retinoblastoma: a curable, rare and deadly blinding disease - Richard Bowman (Community Eye Health Journal, 2018)
Every year, thousands of babies and children in low- and middle-income countries lose their sight and their lives to a treatable childhood eye cancer called retinoblastoma; usually because it was not recognised and treated in time.